Mexico : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
Strong fundamentals and a policy track record helped Mexico to withstand the fallout from the global crisis and aided recovery. The policy challenges have to take due account of significant global uncertainty, employment generation, and long-term fiscal reforms. The economy will benefit from rebuilding fiscal policy buffers over the medium-term. The flexible exchange rate regime has helped Mexico. The long-term challenges include declining oil reserves relative to GDP and population aging. Advancing structural reforms to increase productivity and promote investment will help in increasing the growth potential.